Bayesian luminescence dating at Ghār-e Boof, Iran, provides a new chronology for Middle and Upper Paleolithic in the southern Zagros. Issue 151 (February 2021) - Heydari, Maryam; Guérin, Guillaume; Zeidi, Mohsen; Conard, Nicholas J.
Abstract: Ghār-e Boof is a Paleolithic cave site in Iran well known for its rich early Upper Paleolithic Rostamian assemblages. The site is located on the edge of the Dasht-e Rostam plain in the southern Zagros. Recent excavations by the members of the Tübingen-Iranian Stone Age Research Project at Ghār-e Boof also recovered well-stratified Middle Paleolithic assemblages. Here, we provide the first detailed luminescence chronology for the Middle and Upper Paleolithic of the site. More generally, our work is the first luminescence chronology for a Middle and Upper Paleolithic site in the Zagros Mountains region in Iran. The luminescence ages for the Upper Paleolithic of Ghār-e Boof agree with published 14 C dates. We applied Bayesian models specifically designed for luminescence dating using the R package 'BayLum' to incorporate the well-established stratigraphic constraints, as well as the published 14 C ages with our optically stimulated luminescence (OSL) ages to improve the precision of the chronological framework. The Bayesian chronology shows a significantly improved precision of the OSL ages in particular for the upper part of the sequence where 14 C ages were available. The Bayesian OSL ages for the Rostamian horizons, archaeologicalhorizon (AH) III (a-b-c), and AH IV, fall in the range of 37–42 ka (68% credible interval [CI]). Moreover, we determined a series of dates between 45 and 81 ka (68% CI) for the Middle Paleolithic strata from AH IVd to AH VI. Our results point to a demographic shift in the populations responsible for the Middle Paleolithic and the Rostamian within three millennia. This major technological change accompanied by the rise of symbolic artifacts such as personal ornaments, may or may not reflect a replacement of Neanderthals by modern humans. While we are confident that the Rostamian was made by modern humans, available information does not allow us to be sure who made the local Middle Paleolithic.